Corrigendum to "Renormalised solutions in thermo-visco-plasticity for a Norton–Hoff type model. Part I: The truncated case" [Nonlinear Anal. RWA 28 (2016) 140–152]. (October 2017) - Chełmiński, Krzysztof; Owczarek, Sebastian
Abstract: We correct an error in the original paper [Renormalised solutions in thermo-visco-plasticity for a Norton–Hoff type model. Part I: The truncated case, Nonlinear Anal. RWA 28 (2016) 140–152]. The proof of Theorem 3.2 is wrong and therefore we present here correct proof based on the same methods.